2019
DOI: 10.1093/rheumatology/kez153
|View full text |Cite
|
Sign up to set email alerts
|

Development of semiquantitative ultrasound scoring system to assess cartilage in rheumatoid arthritis

Abstract: Objectives To develop and test the reliability of a new semiquantitative scoring system for the assessment of cartilage changes by ultrasound in a web-based exercise as well as a patient exercise of patients with RA. Methods A taskforce of the Outcome Measures in Rheumatology Ultrasound Working Group performed a systematic literature review on the US assessment of cartilage in RA, followed by a Delphi survey on cartilage chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…For semiquantitative evaluation of RA finger joint cartilage, the 5‐grade evaluation (grades 0–4) reported by Filippucci et al (4) and the 3‐grade evaluation (grades 0–2) reported by the EULAR‐Outcome Measures in Rheumatology (OMERACT) group (5) are currently available. In the current study, we used the 3‐grade evaluation advocated by the EULAR‐OMERACT group because of its favorable feasibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For semiquantitative evaluation of RA finger joint cartilage, the 5‐grade evaluation (grades 0–4) reported by Filippucci et al (4) and the 3‐grade evaluation (grades 0–2) reported by the EULAR‐Outcome Measures in Rheumatology (OMERACT) group (5) are currently available. In the current study, we used the 3‐grade evaluation advocated by the EULAR‐OMERACT group because of its favorable feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…Since the evaluation was of a semiquantitative method, the cartilage measurement was not corrected for the increased speed of sound within it. Furthermore, one US examiner (TO) who was blinded to other medical information performed the semiquantitative scoring of the recorded cartilage images using a scale of 0–2 (0 = normal, 1 = minimal, and 2 = severe) (5) (see Supplementary Figure , available on the Arthritis Care & Research website at http://onlinelibrary.wiley.com/doi/10.1002/acr.24101/abstract).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hands were placed on the table, with the metacarpophalangeal joints in maximal flexion (>60 • ) (14,36,37). The metacarpal head from the 2nd to the 5th digit of both hands was scanned on the dorsal aspect from radial to ulnar and from proximal to distal sides to ensure the maximal exploration of the hyaline cartilage using the EULAR standard scans (38).…”
Section: Us Image Acquisition and Interpretationmentioning
confidence: 99%
“…The main aim of this study was to develop an automatic DL algorithm for US informative-image selection of hyaline cartilage at metacarpal head level. An image was defined informative when it shows enough information to fulfill the Outcome Measure in Rheumatology US definition of healthy hyaline cartilage (36). The algorithm performance and that of three beginner sonographers were compared with an expert assessment, which was considered the gold standard.…”
Section: Introductionmentioning
confidence: 99%